Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fped.2022.943320
|View full text |Cite
|
Sign up to set email alerts
|

Serum Relmβ combined with abdominal signs may predict surgical timing in neonates with NEC: A cohort study

Abstract: AimsTo examine the predictive value of serum biomarkers combined with other indicators for necrotizing enterocolitis (NEC) surgery decision-making.MethodsClinical data, including baseline information, clinical features, imaging presentation and serum assessment, of the infants enrolled were collected, and the serum concentrations of HBD2, HMGB-1, Claudin-3 and Relmβ were determined. Student's t test, the Mann–Whitney U test, the chi-square test and logistic regression analysis were used. Receiver operating cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, we measured the fecal concentration of HMGB-1 and Relmβ in our study. Fecal HMGB-1 has been reported to be helpful in the diagnosis of NEC ( 15 ), and our previous study found that in those needing surgeries, the level of serum Relmβ was even higher ( 12 ). HMGB-1 participates in intestinal inflammation of NEC by inhibiting the NLR pyrin domain containing 3 via Toll-like receptor 4 and nuclear factor-kappaB signaling pathways and decreases intestinal microcirculatory perfusion by rescuing nitric oxide production and eliminating oxygen production through endothelial nitric oxide synthase activation ( 23 , 37 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, we measured the fecal concentration of HMGB-1 and Relmβ in our study. Fecal HMGB-1 has been reported to be helpful in the diagnosis of NEC ( 15 ), and our previous study found that in those needing surgeries, the level of serum Relmβ was even higher ( 12 ). HMGB-1 participates in intestinal inflammation of NEC by inhibiting the NLR pyrin domain containing 3 via Toll-like receptor 4 and nuclear factor-kappaB signaling pathways and decreases intestinal microcirculatory perfusion by rescuing nitric oxide production and eliminating oxygen production through endothelial nitric oxide synthase activation ( 23 , 37 ).…”
Section: Discussionmentioning
confidence: 90%
“…Human β-defensin 2 (HBD-2), Claudin-3, high-mobility group box-1 protein (HMGB-1), and resistin-like molecule β (Relmβ) are potential biomarkers in intestinal inflammation, and they have been proposed as such in the diagnosis of NEC (10)(11)(12)(13)(14)(15). HBD-2 is an antibacterial peptide in the innate immune system of the intestinal mucosa that can regulate the immune response with Toll-like receptor 4 and other recognition receptors to maintain the normal function that is expressed in inflammation but not in normal epithelial tissues (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NEC have been shown to have higher expression of HMGB1 than healthy control counterparts (19,27). Levels of HMGB1 were not substantially different in patients with Stage II or Stage III NEC (when measured in the stool), or patients who were managed medically or surgically (when measured in the serum) (91,92). Nevertheless, HMGB1 levels in stool samples were higher in preterm neonates compared to full-term neonates with birth weight less than 2.5 kg, and early HMGB1 fecal levels were predictive of NEC risk, thus implicating stool HMGB1 as a potential clinical biomarker in this disease (29).…”
Section: High Mobility Group Boxmentioning
confidence: 92%
“…As such, a specific biomarker or panel of biomarkers to specifically identify NEC would be ideal. Investigations continue for biomarkers of NEC, but widespread clinical application of these markers is limited (Table 1) [15 ▪ ,16–20]. Faecal HBD-2 and Claudin-3 may be potential biomarkers to predict the deterioration of NEC from Stage II to Stage III but will need further validation [16].…”
Section: Methods Of Predictionmentioning
confidence: 99%